ANALYSIS OF FOOD AVAILABILITY AND FOOD PATTERN HOPE IN MEDAN CITY IN 2022 - Eliska, Eliska; Pasaribu, Aggridita Agita; Ananda, Vivi Alysa; Turrahma, Mardyah (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Food availability can be defined as a condition where the available food comes from domestic production, food supply, and food income, including imports and food aid, when some important food sources cannot meet their needs. One of the basic human needs is food that must be available and consumed every day to meet needs and sustain life. Food can be more easily accessed if the food is available in quantity and quality that meets the needs of the community. This study aims to determine the condition of food availability and food expectancy patterns in Medan City. The methods used in this study are qualitative methods and description approaches. The result obtained is that food production in the city of Medan has changed from year to year. The availability of most widely available food for consumption is rice amounting to 334.52 grams/capita/day. While the type of food consumed the least is garlic amounting to 1.91 grams/capita/day. The existing community's PPH score value is still below the maximum PPH score, however, it has improved in quality and quantity, which is 92.9. Efforts that can be made to increase food availability are by directing OPD related to community consumption which focuses on B2SA-based household consumption practices.